Early Postoperative Complications Following Modified Radical Mastectomy with Level II Axillary Clearance - Shah Abbass, Muhammad Nadeem, Haider Shah, Shahzad Khan, Anwar Ul Haq, Shahid Alam (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: This study aims to identify the most common early postoperative complications experienced by patients undergoing modified radical mastectomy with level II axillary clearance for early-stage breast cancer and to assess the statistical significance of these complications. Study Design: Descriptive, retrospective study Place and Duration: Conducted at the Surgical B Unit, Saidu Teaching Hospital Swat during from May 2023 to October 2023. Methods: A total of 125 female patients diagnosed with early-stage breast cancer who underwent a modified radical mastectomy with level II axillary clearance were monitored for up to one month post-surgery. The occurrence of complications was recorded, and statistical analysis was performed using SPSS 24.0, with a p-value of < 0.05 considered statistically significant. Results: The mean age of the patients was 50.12 ± 7.44 years. The most frequent complication was seroma formation, which occurred in 44 patients (35.2%). This was followed by arm edema in 31 patients (24.8%) and wound infection in 14 patients (11.2%). Other complications included paresthesia in 11 patients (8.8%), hemorrhage and hematoma in 7 patients (5.6%), skin flap necrosis in 6 patients (4.8%), and muscle paralysis of the serratus anterior and Latissimus Dorsi in 4 patients (3.2%). Statistical analysis revealed a significant association between complications and clinical outcomes (p < 0.05). Conclusion: The study highlights that seroma formation, arm edema, wound infection, and paresthesia are the most common early complications following modified radical mastectomy with level II axillary clearance. Less frequent but notable complications include hemorrhage, hematoma, skin flap necrosis, and muscle paralysis. Early detection and effective postoperative care are essential in managing these complications and improving patient outcomes. Keywords: Early Complications, Modified Radical Mastectomy, Axillary Clearance, Seroma Formation, Postoperative Care